INHIBITION OF STREPTOCOCCUS MUTANT GROWTH BY PURPLE LEAF EXTRACT (Graptophyllum pictum) - Tiarisna Hidayatun Nisa; Tegar Permadi Dimas Prakoso (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Tooth decay is an infectious disease of microbial origin. Considering the increasing prevalence of antibiotic resistance due to their overuse and also their side effects, medicinal plants are now considered for use against bacterial infections. This study aimed to assess the effects of Graptophyllum pictum extract on inhibition of Streptococcus mutans. In this experimental study, serial dilutions of the extract were prepared in 13 test tubes for each bacterium. Standard amounts of bacterial suspension were added; 100ƛ of each tube was cultured on prepared solid agar plates and incubated at 37°C for 24 hours.Serial dilutions of the extract were prepared in another 20 tubes and 100ƛ of each tube was added to blood agar culture medium while being prepared. The mixture was transferred to the plates. The bacteria were inoculated on plates and incubated as described. The minimum inhibitory concentration (MIC) was 0.04 mg/mL for S. mutans. The minimum bactericidal concentration (MBC) was 0.09 mg for S. mutans. Conclusion. Graptophyllum pictum extract has significant antibacterial activity against S. mutans cariogenic microorganisms. Keyword: inhibition, Streptococcus Mutan, Graptophyllum pictum.